2021
DOI: 10.3389/fneur.2021.677888
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Examination of Sharp/Dull Discrimination as Clinical Measure of Spinothalamic Tract Integrity

Abstract: Objective: Revisiting the sharp/dull discrimination as clinical measure of spinothalamic tract function considering the International Standards for Neurological Classification of Spinal Cord Injury (ISNCSCI). Three clinically relevant factors were evaluated as to their impact on reliability: (1) the localization of dermatomes in relation to the sensory level, (2) the examination tool, and (3) the threshold of correct answers for grading of a preserved sharp/dull discrimination.Design: Prospective monocentric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…An association between pain and structural changes of the sciatic nerve could not be found for MRN parameters of the sciatic nerve in our cohort, which may be due to the fact that it is not yet possible to discriminate between sensory and motor fiber lesions in mixed peripheral nerves using MRN. In addition, it is possible that the transmission of sensory input from the PNS to cortical regions may be completely interrupted in some of the SCI participants, particularly considering that most of the participants in the present cohort were characterized by a clinically complete SCI (AIS A) [37]. Hence, individuals characterized by such a lesion pattern may not perceive painful symptoms, albeit displaying structural changes in the PNS and being susceptible to neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An association between pain and structural changes of the sciatic nerve could not be found for MRN parameters of the sciatic nerve in our cohort, which may be due to the fact that it is not yet possible to discriminate between sensory and motor fiber lesions in mixed peripheral nerves using MRN. In addition, it is possible that the transmission of sensory input from the PNS to cortical regions may be completely interrupted in some of the SCI participants, particularly considering that most of the participants in the present cohort were characterized by a clinically complete SCI (AIS A) [37]. Hence, individuals characterized by such a lesion pattern may not perceive painful symptoms, albeit displaying structural changes in the PNS and being susceptible to neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…ent cohort were characterized by a clinically complete SCI (AIS A)[37]. Hence, individuals characterized by such a lesion pattern may not perceive painful symptoms, albeit displaying structural changes in the PNS and being susceptible to neuropathic pain.…”
mentioning
confidence: 99%
“…5 The ISNCSCI guideline recommends use of a safety pin, as studies in adults with spinal cord injuries demonstrate that the use of the safety pin provides a more reliable examination when compared to use of a Transofix, Nerotip, or cotton tip. 6 However, two separate multicenter studies found that patients younger than the age of 6 were unable to accurately differentiate pinprick, making traditional AIS scoring inaccessible for this population. 7,8 The spinothalamic tract carries information for both pain and temperature, 9 and accurate assessment of spinothalamic tract integrity has important implications in prediction of neurogenic recovery of bladder function in spinal cord injury.…”
mentioning
confidence: 99%